Expert consensus-based clinical recommendation for an integrative anthroposophic treatment of acute bronchitis in children: A Delphi survey - Pilar Marie Wopker; Melanie Schwermer; Simon Sommer; Alfred Längler; Katharina Fetz; Thomas Ostermann; Tycho Jan Zuzak (Elsevier, 2021)
Background: Acute bronchitis is one of the most common pediatric diseases. In addition to conventional therapies, a frequent use of complementary and alternative medicine (CAM) has been stated. Anthroposophic medicine (AM) is one of the most practiced complementary and integrative medicine (CIM) approaches in Central Europe but hitherto no consensus-based clinical recommendations or guidelines are available.Therefore, a consensus-based recommendation leading to an informed and reasonable use of AM in the treatment of acute bronchitis in pediatrics was developed. Methods: A total of 61 physicians in Germany with expertise in the field of anthroposophic pediatrics was invited to complete an online multistep Delphi process. Two independent reviewers quantitatively and qualitatively evaluated the results. The survey was completed when >75 % consensus was achieved. Results: The clinical recommendation comprises 15 subitems related to treatment as well as clinical and psychosocial aspects. All items reached strong consensus (>90 %; N = 9) or consensus (75-90 %; N = 6). Conclusion: The comprehensive clinical recommendation creates a scientific base for the anthroposophic integrative treatment of acute bronchitis in children in Germany. It will make the anthroposophic approach more applicable, understandable and comparable to a wider public of physicians and other health professionals in Germany.